Identidades profissionais: um estudo de narrativas (auto)biográficas de professores de oboé - Mota, Lúcius Batista (2017)
This thesis is the result of a qualitative research based on interviews carried out with sixteen oboe teachers from different states, including the South, Southeast, Midwest and Northeast regions. The in-person interviews conducted can be classified as narratives (JOVCHELEVITCH; BAUER, 2002), or episodic storytelling (FLICK, 2002). Because the interviews dealt with several phases of the interviewees' lives and career, the research acquired a (auto) biographical profile (BOLIVAR, 2002; FERRAROTI, 2014). The data were analyzed through the Grounded Theory (CHARMAZ, 2009). The research initially aimed to understand the relationship between the professional identity of oboe teachers and the way they deal with issues such as teaching, the place of music in the university, the different learning spaces, among others. From a theoretical point of view, two books by Claude Dubar (2005; 2009) play a central role throughout the thesis. The discussion regarding the identity of artists who teach was based on texts written by Louro (2004), Almeida (2009), Arruda (2012) and Thornton (2012), which address the artist's relationship with the academy. Two concepts are proposed in order to contribute to the understanding of the identity of oboe teachers: Oboe World and body technologies. The thesis is divided into five sections: Theoreticalmethodological paths; Learning, which discusses the teachers’ Educational process; Teaching that seek to understand the pedagogical theory of each one; Living, which it is discussed how the identity of oboist is related to the different places of work; and the Conclusion, that proposes that there is a strong identity of oboist, around which, as the metaphor of the Sunflower (LOURO, 2004) revolve the many faces of the respondents. Despite several chances that the area of ARTS/MUSIC has undergone in recent decades, there is still conflict between teachers in the parameters of artistc production, in particular in the post-graduation. Between each of the major sections, a prelude, interludes, and postlude were included, which adopted a freer, more subjective and literary style, in contrast to the more formal writing of the rest of the work.